Effect of Magnetized Water and Seeds on the Growth and Yield of Sesame (Sesamum indicum L.) under Irrigation - Ahmed, Faisal E.; Mohammed, Zeinab I. (University of Khartoum Journal of Agricultural Sciences, 2023)
Magnetic treatment is hypothesized to result in the improvement of the performance of some crops. A field study was conducted to evaluate the effect of magnetized water and seeds on growth and yield of sesame (cv. Promo). An experiment was carried out for two consecutive seasons (2004/05 and 2005/06) in the Demonstration Farm, Faculty of Agriculture, Shambat, Sudan. The seeds were either sown directly or after passing them through a magnetic field. The crop received equal quantities of either normal or magnetized water every 14 days. The results showed that magnetized water and seeds consistently had non- significant positive effect on mean plant height, number of leaves per plant and stem diameter. The plants irrigated with magnetized water took significantly fewer days to flower than their respective untreated plants. Magnetized water and seeds significantly increased seed yield due to increased number of capsules per plant. In contrast, all treatments had no significant effect on mean 1000-seed weight and oil content of seeds.